Innocence and experience: early childhood education and industrialisation in England and Wales, 1767-1876 - Henderson, L (2024)
This thesis argues that early childhood learning played a crucial role in shaping the skills of the adult workforce during the first industrial revolution in England and Wales. Drawing on a mix of economic, historical, and psychological perspectives, I highlight the theoretical importance of `sensitive periods' for learning and analyse historical educational provision at the turn of the nineteenth century from a life-course perspective. In particular, I suggest that changing how education was distributed across early and late childhood could result in higher levels of human capital under certain conditions. I demonstrate that customary school-entry age varied widely, and many children did not attend school until very late by contemporary standards. Additionally, I examine the intellectual influence of Locke, Darwin, and Rousseau, among others, to argue that a more developmental theory of learning only rose to prominence in the later nineteenth century. I argue that under these conditions, earlier school enrolment would improve human capital outcomes. Earlier school enrollment derived from greater child-care demand, as schools provided child care and education jointly and had developed to effectively meet the needs of young children. Where mothers and elder siblings who would otherwise be caring for young children participated more intensively in the labour market, the demand for child-care arose earlier in the household life-cycle. Using a case study of London between 1760 and 1830 and a detailed analysis of the 1851 census returns, I demonstrate that higher female wages, and to a lesser extent demographic factors like smaller family size and longer spacing between surviving children, led children to attend school earlier over time and in areas where women and children were employed in industry. I also demonstrate that early education was associated with a more rapid acquisition of basic literacy and likely made subsequent skill development more efficient.